The mediating effect of life complexity and dynamic, and work-life conflict on the effect of motivation on continuance commitment and quality of life of female factory workers in Jabodetabek - Sylvia Diana Purba; Christine Winstinindah Winstinindah (Universitas Hayam Wuruk Perbanas, 2016)
Motivation arising due to the need can be a factor that increases continuance com-mitment to an organization, which is expected to have an effect on the improvement of the quality of life. This research was conducted on 126 female factory workers who are already married and have children. This study aims to examine the mediating effect of life complexity and dynamic and work-life conflict on the effect of commit-ment on continuance commitment and quality of life of the respondents. The results could not prove the significant influence of motivation on the quality of life, either directly or through the mediation of life complexity and dynamic, work life conflict and continuance commitment. Despite a high-perceived value, motivation has no significant positive effect on the quality of life of female factory workers. Other re-sults found in this study show the direct influence of motivation in improving con-tinuance commitment, in which the influence is significant and strong. Meanwhile, life complexity, dynamics, and work-life conflict, as the mediating factors, also have significantly and positively weak influence.